The Hidden Resolution Approach by Madurese Ulama as A Community-Based Model of Religious Conflict Prevention and Resolution - Limas Dodi (IAIN Ponorogo, 2021)
Abstract: This study aims to describe the role of the Madurese Ulama in preventing and resolving religious conflicts. The depiction of the part of the Madurese ulema in organizing the socio-religious system can be used as an example of religious conflict resolution at local and even global levels. This research is qualitative with a descriptive analysis approach, an approach that explores socio-religious phenomena. The data were obtained directly from Ulama (clerics), congregations or members of religious sects, and leaders of religious organizations using interview and documentation methods. This research found several essential things. First, a form of religious conflict in the Madura region in the form of an internal conflict of followers of Islam which has three conditions; 1) socio-economic based religious conflict, 2) community-based religious sect conflict, and 3) sectarian religious conflict based on institutional authority. The conflict resolution model that the scholars are fighting is 1) the hidden resolution), 2) the hidden reconciliation model, 3) the hidden filtered. This finding has implications for three things: 1) We can suppress the construction of conflict resolution, the roots of sensitivity to religious conflicts through secure means; 2) causality between religion, economy, and society gives rise to the ideal construct of conflict resolution; 3) religious authorities are more effective in acting as closed mediators in conflict reconciliation.الملخص: تهدف هذه الدراسة إلى وصف دور علماء المادوريين فضلا في منع النزاعات مع الفروق الدينية وحلها. يمكن استخدام دور علماء المادوريين في إدارة النظام الاجتماعي والديني كمثال على حل النزاعات الدينية محليا وعالميا. هذا البحث نوعي بمنهج التحليل الوصفي ، وهو منهج يستكشف الظواهر الاجتماعية لدرجة تشبع العلماء والتجمعات الدينية ورؤساء المنظمات الدينية من خلال تقنيات المقابلة والتوثيق. وتوصل البحث إلى عدة أمور مهمة ، أبرزها الشكل الأول للصراع الديني في منطقة مادورا على شكل صراع داخلي بين أتباع الإسلام له ثلاثة أشكال ؛ 1) صراع الطوائف الدينية على أساس اقتصاديات اجتماعية ، 2) صراع الطوائف الدينية على أساس المجتمع ، 3) صراع الطوائف الدينية على أساس السلطة المؤسسية. أما نماذج حل النزاع التي يلعبها العلماء هي: 1) نموذج مقنع مغلق (قرار مخفي) ، 2) نموذج مصالحة مغلقة (تسوية خفية) ، 3) تصفية مغلقة (تصفية مخفية). هذه النتيجة لها آثار على ثلاثة أشياء: 1) بناء حل النزاع ، يمكن قمع جذور الحساسية للنزاعات الدينية من خلال وسائل مغلقة. 2) تؤدي العلاقة السببية بين الدين والاقتصاد والمجتمع إلى تكوين البنية المثالية لحل النزاع ؛ 3) السلطات الدينية أكثر فاعلية في العمل كوسطاء مغلقين في تسوية النزاعات.Abstrak: Penelitian ini bertujuan untuk menggambarkan secara detail tentang peran ulama Madura dalam mencegah dan menyelesaikan konflik bernuansa agama. Penggambaran peran ulama Madura menata tatanan sistem sosial keagamaan dapat dijadikan contoh resolusi konflik agama baik di tingkat lokal bahkan global. Penelitian ini bersifat kualitatif dengan pendekatan deskriptif analisis, suatu pendekatan yang menggali fenomena sosial sampai jenuh dari para ulama, jemaah aliran keagamaan dan ketua organisasi keagamaan melalui teknik wawancara dan dokumentasi. Dari penelitian tersebut ditemukan beberapa hal penting, yaitu pertama bentuk konflik keagamaan di wilayah Madura berupa konflik internal penganut agama Islam yang memiliki tiga bentuk; 1) konflik aliran keagamaan berbasis pada sosio-ekonomi, 2) konflik aliran keagamaan berbasis komunitas masyarakat, dan 3) konflik aliran keagamaan bebasis pada otoritas kelembagaaan. Model resolusi konflik yang diperankan ulama adalah: 1) model persuasif tertutup (hidden resolution), 2) model rekonsiliasi tertutup (hidden reconciliation), 3) filterasi tertutup (hidden filtered). Temuan ini berimplikasi pada tiga hal: 1) konstruk resolusi konflik, akar sensitifitas konflik keagamaan dapat diredam melalui cara-cara tertutup; 2) kausalitas antara agama, ekonomi dan sosial memunculkan konstruk ideal resolusi konflik; 3) otoritas agama lebih efektif berperan sebagai mediator tertutup dalam rekonsialisi konflik.